Bede and the cosmos theology and nature in the eighth century - Ahern, Eoghan (Studies in early medieval Britain and Ireland, 2020)
"Bede and the Cosmos examines Bede's cosmology-his understanding of the universe and its laws. It explores his ideas regarding both the structure and mechanics of the created world and the relationship of that world to its Creator. Beginning with On the Nature of Things and moving on to survey his writings in other genres, it demonstrates the key role that natural philosophy played in shaping Bede's worldview, and explores the ramifications that this had on his cultural, theological and historical thought. From questions about angelic bodies and the destruction of the world at judgement day, to subtle arguments about free will and the meaning of history, Bede's fascinating and unique engagement with the natural world is explored in this comprehensive study"--